Child Growth and Development - Paris, Jennifer; Ricardo, Antoinette; Rymond, Dawn (Open textbook library., 2019)
Welcome to Child Growth and Development. This text is a presentation of how and why children grow, develop, and learn. We will look at how we change physically over time from conception through adolescence. We examine cognitive change, or how our ability to think and remember changes over the first 20 years or so of life. And we will look at how our emotions, psychological state, and social relationships change throughout childhood and adolescence.